Pengujian sensoris nugget mawar sebagai panganan vegetarian - Haning Hasbiyati; Diah Sudiarti; Siti Roudlotul Hikamah (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
One type of food consumed by vegetarians is nugget by developing innovations of rose petals into food nugget which has a good taste, it will attract the community as vegetarian food. Therefore, it is necessary to conduct sensory testing related to the innovation of rose nuggets. This study consists of several stages, namely the making of rose petal nuggets starting with the manufacturing trial. The formulation obtained from the results of the trial preparation will be conducted by sensory testing of panelists on color, aroma, taste, and texture with three comparisons of substitution formulas. In procuring the raw material for roses for processing nuggets, the results of the roses treatment test after the harvesting process have an effect on the product yield. As a result of the eight times test, we obtained the method and loading material for rose petals. Based on the results of sensory testing it was found that formulation B achieved the highest average value. On the average color specifications panelists give the highest value in formulation B of 88.89, on the aroma specifications the highest value in formulation B is 92.59, in the specification of the highest value in formulation B is 98.15, and on the highest value texture specifications in formulation B is 99.26. Based on the test results of preference also obtained that formulation B achieved the highest average value.